PENGARUH ORIENTASI SERAT KOMPOSIT E-GLASS EPOXY TERHADAP SIFAT MEKANIK PEGAS DAUN TUNGGAL DENGAN METODE ELEMEN HINGGA - Kusmiran, Amirin; Desiasni, Rita (Jurnal TAMBORA, 2020)
Single leaf spring is one of the suspension systems on vehicles that function as vibration dampers which usually use steel. One type of steel that is often used in making single leaf springs is 55Si7 steel. However, at this time composite materials began to be used as an alternative material to replace steel. One of the composite materials used as a substitute for steel is E-glass epoxy. This study aims to determine differences in the characteristics of steel leaf springs and e-glass epoxy composites. In addition, the effect of orientation of the fiber direction to deformation, stress, and safety factors on leaf springs was also carried out in this study. The analytical method used is finite element. The results showed that the composite leaf springs had lower stress than steel leaf springs. E-glass epoxy composite leaf springs variation D (fiber orientation 45Âº / -45Âº) showed the lowest stress and highest safety factor with values ??of 596 MPa and 1.4 respectively.